Evaluation of serum uric acid level in psoriatic patients at Tishreen University Hospital, 2020 - Roumie, AbdulHalim Ahmad; Farrouh, Shireen Mohamed (Journal of medical and pharmaceutical sciences, 2022)
Background: Psoriasis is a common chronic skin disease. Hyperuricemia is a common finding in patients with psoriasis. However, previous studies have reported inconsistent results about the association between serum uric acid concentration and psoriasis. Aim: This study was designed to find out the association between serum uric acid levels and psoriasis. Materials and Methods: This was a case - control study conducted at Tishreen University Hospital, Lattakia, during the period between June 2020 and June 2021. 60 Patients diagnosed as having psoriasis and 60 age and sex matched apparently healthy volunteers(as controls) were studied after taking their consent. Detailed history and clinical examination were performed, laboratory values of serum uric acid level and Psoriasis Area and Severity Index (PASI) score were assessed. Results: Patients with psoriasis had higher uric acid levels than controls (5.7 ± 1.1versus 5.2± 1.2 mg/dl, P<0.05), and higher prevalence of asymptomatic hyperuricemia (21.7% versus 8.3%. P<0.05). There was no association between age, sex, or clinical type of psoriasis and hyperuricemia (P > 0.05). BMI and duration of the disease were correlated with uric acid concentration (P < 0.05). There was a positive correlation between serum uric acid and PASI in patients with psoriasis (P < 0.05). Conclusion: Serum uric acid in patients with psoriasis is positively associated with PASI, BMI, and duration of the disease.